Influence of the Probiotic Lactobacillus acidophilus NCFM and Lactobacillus rhamnosus HN001 on Proteolysis Patterns of Edam Cheese - Marek Aljewicz; Grażyna Cichosz; Beata Nalepa; Marika Kowalska (Food Technology and Biotechnology, 2014)
The objective of this study is to determine the viability of Lactobacillus acidophilus NCFM and Lactobacillus rhamnosus HN001 in Edam cheese as well as the effect of probiotic bacteria on paracasein proteolysis and changes in the water activity during ripening. The use of probiotics L. rhamnosus HN001 and L. acidophilus NCFM in Edam cheese slightly changed its chemical composition, but the change was not significant. The pH values were significantly correlated with the changes in Lactobacillus count (R=–0.807) and the level of phosphotungstic acid-soluble nitrogen compounds in total nitrogen (PTA-SN/TN) (R=0.775). After 10 weeks of ripening, the highest level of trichloroacetic acid-soluble nitrogen compounds in total nitrogen (TCA-SN/TN) was observed in the cheese containing L. rhamnosus HN001 (11.87 %) and slightly lower level in the cheese containing L. acidophilus NCFM (7.60 %) and control cheese (6.24 %). The highest level of PTA-SN/TN fraction was noted in cheese containing L. acidophilus NCFM (3.48 %) but the lowest level was observed in control cheese (2.24 %) after ten weeks of ripening. The changes in the levels of PTA-SN/TN (R=–0.813) and TCA-SN/TN (R=–0.717) fractions were signifi cantly (p<0.05) correlated with the viability of probiotic counts. Water activity (aw) strongly correlated with the PTA-SN/TN level (R=–0.824) and bacteria viability (R=–0.728). All of the analyzed cheeses were characterized by high counts of L. rhamnosus HN001 and L. acidophilus NCFM during ten weeks of ripening.